The Ideal Character of Indonesian Counselors Based on The Noble Values of The Trident of Kiai Musta'in Romly's Thought: A Study in Hermeneutic Perspective - Bakhrudin All Habsy (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2025)
: This study is based on the integrity of the Indonesian counselor's self-identity as an effort to gain expertise in the implementation of socio-religious-based counseling practices through down-to-earth views typical of Indonesian culture, not only theoretical views that are mostly developed by counseling figures who adhere to Western philosophies. One of the noble values of the Indonesian nation based on Islamic Archipelago culture is the trident teaching of Kiai Musta'in Romly's thoughts with some noble values, namely: 1) Obedience, 2) Diligence, 3) Honesty, 4) Patience, and 5) Sincerity. Kiai Musta'in Romly's trident of noble values produces a deep philosophy and presents a new view of the basic attitude of Indonesian counselors, and becomes a reference in the practice of counseling typical of Indonesian culture. The focus of this research is the identification of the noble values of the trident of Kiai Musta'in Romly's thought as a socio-religious-based construction of the Ideal Counselor character.